Biopharmaceutical research on the choice of a non-steroidal anti-inflammatory agent in the development of combination gel for mastopathy therapy - Zuikina, S; Vyshnevska, L (Annals of Mechnikov’s Institute, 2020)
According to the International Agency for Research on Cancer (IARC) at WHO, more than 1.7 million women are diagnosed with breast cancer annually. In Ukraine, according to the National Cancer Registry, in 2013, BC was first identified in 16,624 women (in 2012 – 16,660), which is 72.2 cases (in 2012 – 67) for every 100,000 women in the country. The global death toll from this disease is growing and is killing more than 500,000 women worldwide annually. According to experts from the National Cancer Institute, a diagnosis of breast cancer by the end of 2020 may become a reality for almost 17% of Ukrainian women, which gives reason to view it as a socially significant epidemiological problem. The aim of the study was to substantiate the choice of NSAIDs and their concentration for use in the development of combination gel for the treatment of mastopathy and prevention of breast cancer. The methods of literary analysis, marketing research and biopharmaceutical methods in vitro were used. The results of marketing studies and pharmacological studies of the level and types of activity of NSAIDs allowed indometacin to be selected as the active pharmaceutical ingredient (API). According to the results of biopharmaceutical studies, the concentration of the active substance in the composition of the gel is established. DOI: 10.5281/zenodo.4038892